Bioethics Methods in the Ethical, Legal, and Social Implications of the Human Genome Project Literature. (24th June 2013) - Walker, Rebecca L.; Morrissey, Clair
Abstract While bioethics as a field has concerned itself with methodological issues since the early years, there has been no systematic examination of how ethics is incorporated into research on the Ethical, Legal and Social Implications (ELSI) of the Human Genome Project. Yet ELSI research may bear a particular burden of investigating and substantiating its methods given public funding, an explicitly cross‐disciplinary approach, and the perceived significance of adequate responsiveness to advances in genomics. We undertook a qualitative content analysis of a sample of ELSI publications appearing between 2003 and 2008 with the aim of better understanding the methods, aims, and approaches to ethics that ELSI researchers employ. We found that the aims of ethics within ELSI are largely prescriptive and address multiple groups. We also found that the bioethics methods used in the ELSI literature are both diverse between publications and multiple within publications, but are usually not themselves discussed or employed as suggested by bioethics method proponents. Ethics in ELSI is also sometimes undistinguished from related inquiries (such as social, legal, or political investigations).